Synthetic cannabinoid JWH-018 and its halogenated derivatives JWH-018-Cl and JWH-018-Br impair Novel Object Recognition in mice: Behavioral, electrophysiological and neurochemical evidence. (October 2016) - Barbieri, M.; Ossato, A.; Canazza, I.; Trapella, C.; Borelli, A.C.; Beggiato, S.; Rimondo, C.; Serpelloni, G.; Ferraro, L.; Marti, M.
Abstract: It is well known that an impairment of learning and memory function is one of the major physiological effects caused by natural or synthetic cannabinoid consumption in rodents, nonhuman primates and in humans. JWH-018 and its halogenated derivatives (JWH-018-Cl and JWH-018-Br) are synthetic CB1 /CB2 cannabinoid agonists, illegally marketed as "Spice" and "herbal blend" for their Cannabis-like psychoactive effects. In the present study the effects of acute exposure to JWH-018, JWH-018-Cl, JWH-018-Br (JWH-018-R compounds) and Δ 9 -THC (for comparison) on Novel Object Recognition test (NOR) has been investigated in mice. Moreover, to better characterize the effects of JWH-018-R compounds on memory function, in vitro electrophysiological and neurochemical studies in hippocampal preparations have been performed. JWH-018, JWH-018-Cl and JWH-018-Br dose-dependently impaired both short- and long-memory retention in mice (respectively 2 and 24 h after training session). Their effects resulted more potent respect to that evoked by Δ 9 -THC. Moreover, in vitro studies showed as JWH-018-R compounds negatively affected electrically evoked synaptic transmission, LTP and aminoacid (glutamate and GABA) release in hippocampal slices. Behavioral, electrophysiological and neurochemical effects were fully prevented by CB1 receptor antagonist AM251 pretreatment, suggesting a CB1 receptor involvement. These data support the hypothesis that synthetic JWH-018-R compounds, as Δ 9 -THC, impair cognitive function in mice by interfering with hippocampal synaptic transmission and memory mechanisms. This data outline the danger that the use and/or abuse of these synthetic cannabinoids may represent for the cognitive process in human consumer. Highlights: JWH-018-Cl and -Br are new halogenated cannabinoids seized in Internet Market. JWH-018-R compounds impair short and long term working memory in mice. JWH-018 reduced K + -evoked glutamate and GABA release from hippocampal slices. JWH-018-R compounds affected the synaptic excitatory transmission in mouse model.